2021
DOI: 10.3329/jsr.v13i2.49777
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Incidence of Diseases in Cattle and Goat at Different Area of Bera Upzilla in Pabna District of Bangladesh

Abstract: Ruminant, especially cattle and goats constitute the major portion of the livestock which are usually suffered from a wide range of diseases. Hence, this study was designed to determine clinical cases of cattle and goat in relation to different parameter. A total of 106 sick ruminants (cattle = 56, goat = 50) in different area of Bera upzilla, Pabna were investigated during March to September, 2016. The parasitic infestation (32.1%) in cattle and viral diseases (36%) in goat were higher. In relation to sex, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
2
1
0
Order By: Relevance
“…This observation supports the earlier reports of Samad (2001), Rahman et al (2012), Karim et al (2014), andMajumder et al (2022). This study found that the prevalence of parasitic diseases (30.16%), infectious diseases (21.84%), general systemic states (20.12%) and digestive disorders (18.55%) were significantly higher (P<0.001) among the ten disease categories, which is consistent with the findings of Alam et al ( 2018 This study found 30.16% of cattle with parasitic diseases, which is comparable to earlier studies that found 30.64%-33.86% of cattle with parasitic diseases (Badruzzaman et al, 2015;Juli et al, 2015;Sarker et al, 2015;Meher et al, 2021). However, Mostari et al (2020) reported a lower (8.91%) and Rahman et al (2012) reported a higher (50.40%) prevalence of parasitic diseases in cattle.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This observation supports the earlier reports of Samad (2001), Rahman et al (2012), Karim et al (2014), andMajumder et al (2022). This study found that the prevalence of parasitic diseases (30.16%), infectious diseases (21.84%), general systemic states (20.12%) and digestive disorders (18.55%) were significantly higher (P<0.001) among the ten disease categories, which is consistent with the findings of Alam et al ( 2018 This study found 30.16% of cattle with parasitic diseases, which is comparable to earlier studies that found 30.64%-33.86% of cattle with parasitic diseases (Badruzzaman et al, 2015;Juli et al, 2015;Sarker et al, 2015;Meher et al, 2021). However, Mostari et al (2020) reported a lower (8.91%) and Rahman et al (2012) reported a higher (50.40%) prevalence of parasitic diseases in cattle.…”
Section: Discussionsupporting
confidence: 91%
“…The low occurrence of clinical diseases in calves is attributable to acquired maternal immunity as well as the fact that they do not come into direct contact with contaminated feed. Male cattle (51.78%) were significantly (P < 0.05) more susceptible to diseases than females, which corresponds to the findings of and Meher et al (2021), but differs from the findings of others (Lucky et al, 2016;Rahman et al, 2017;Alam et al, 2018;Majumder et al, 2022). Surgical cases were insignificantly higher in male cattle, which is consistent with the findings of Hossain et al (2016) but contradictory to the findings of Mannan et al (2009).…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 61%
See 1 more Smart Citation